Greece in the European Union - Dimitrakopoulos, Dionyssis G., 1969-; Passas, Argyrēs (Europe and the nation state, 2004)
The contributors collected here discuss the patterns of continuity and change, success and failure observed in seven policy areas - environment, social regulation, regional policy, the single market, agriculture, EMU and foreign policy - in order to investigate how policy formulated and implemented in Greece has changed as a result of EU membership; why Greek authorities have managed to implement EU policy more successfully in some policy areas than in others and whether Greek public opinion vis-à-vis the EU changed over time. This book argues that although the widely-held belief that G.